2016
DOI: 10.1007/s11103-016-0469-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics to decipher the ascorbic acid metabolic network in tomato

Abstract: Ascorbic acid is involved in a plethora of reactions in both plant and animal metabolism. It plays an essential role neutralizing free radicals and acting as enzyme co-factor in several reaction. Since humans are ascorbate auxotrophs, enhancing the nutritional quality of a widely consumed vegetable like tomato is a desirable goal. Although the main reactions of the ascorbate biosynthesis, recycling and translocation pathways have been characterized, the assignment of tomato genes to each enzymatic step of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 98 publications
2
23
0
Order By: Relevance
“…The landrace PDVIT was the best performer, with a mean value over 500 μg g −1 FW. These values are in line with the values previously reported for tomato genotypes, where AsA ranged from 100 to 880 μg g −1 FW, even though commercial cultivars are generally characterized by lower contents (from 100 to 400 μg g −1 FW), probably due to the breeding process . However, the AsA content in fresh tomato fruits is also dependent on genotype, climatic conditions, fruit development, and maturation …”
Section: Resultssupporting
confidence: 91%
“…The landrace PDVIT was the best performer, with a mean value over 500 μg g −1 FW. These values are in line with the values previously reported for tomato genotypes, where AsA ranged from 100 to 880 μg g −1 FW, even though commercial cultivars are generally characterized by lower contents (from 100 to 400 μg g −1 FW), probably due to the breeding process . However, the AsA content in fresh tomato fruits is also dependent on genotype, climatic conditions, fruit development, and maturation …”
Section: Resultssupporting
confidence: 91%
“…; Ruggieri et al . ). These studies show that, for example, the enzymes gluconolactonase, as well as l ‐gulonolactone oxidase, are absent in the genomes of higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…The product L-gulono-1,4-lactone is then finally oxidised to L-AsA. Using bioinformatics Ruggieri et al (2016) found some candidate genes in tomato for the reductase (first step ③ in Fig. 1) but no candidate gene for the second step.…”
Section: Introductionmentioning
confidence: 99%
“…An inventory of 378 candidate genes representing possible targets for antioxidant metabolism in tomatoes was compiled from published literature, previous research 31 , 32 and exploration of metabolic pathway databases (LycoCyc at http://solgenomics.net/and KEGG at http://www.genome.jp/kegg/). Genes were also selected to represent different gene family sizes.…”
Section: Methodsmentioning
confidence: 99%